The Predictive Value of Adipokines and Metabolic Risk Factors for Dropouts and Treatment Outcomes in Children With Obesity Treated in a Pediatric Rehabilitation Center - Vermeiren, Eline; Van Eyck, Annelies; Van De Maele, Karolien; Ysebaert, Marijke; Makhout, Sanae; De Guchtenaere, Ann; Van Helvoirt, Maria; Tanghe, Ann; Naets, Tiffany; Vervoort, Leentje; Braet, Caroline; Bruyndonckx, Luc; et al. (Frontiers in Endocrinology, 2022)
Background Dropouts and weight regain threaten long-term results of inpatient pediatric obesity programs. Preliminary data indicate that leptin, adiponectin, and cardiometabolic comorbidities might predict treatment outcomes. Previous studies have mainly focused on the individual role of adipokines and comorbidities, which is counterintuitive, as these risk factors tend to cluster. This study aimed to predict the dropouts and treatment outcomes by pre-treatment patient characteristics extended with cardiometabolic comorbidities (individually and in total) and adipokines. Methods Children aged 8–18 years participating in a 12-month inpatient program were assessed at pre-treatment, post-treatment, and 6 months post-treatment. Anthropometric data were collected at each visit. Pre-treatment lipid profiles; glucose, insulin, leptin, adiponectin and blood pressure were measured. The treatment outcome was evaluated by the change in BMI SDS. Results We recruited 144 children (mean age of 14.3  2.2 years and mean BMI SDS of 2.7  0.4). The 57 patients who dropped out during treatment and the 44 patients who dropped out during aftercare had a higher pre-treatment BMI compared to the patients who completed treatment (mean BMI, 38.3  6.8 kg/m2 vs 35.7  5.5 kg/m2) and those who completed aftercare (mean BMI, 34.6  5.3 kg/m2 vs 37.7  6.3 kg/m2) (all p<0.05). Additionally, aftercare attenders were younger than non-attenders (mean age, 13.4  2.3 years vs 14.9  2.0, p<0.05). Patients lost on average 1.0  0.4 SDS during treatment and regained 0.4  0.3 SDS post-treatment corresponding to a regain of 43  27% of their previously lost BMI SDS. A higher BMI and more comorbidities inversely predicted BMI SDS reduction in linear regression (all p<0.05). The absolute BMI SDS increase after returning home was predicted by pre-treatment leptin and systolic blood pressure, whereas the post-treatment BMI SDS regain was predicted by pre-treatment age, leptin, and adiponectin levels (all p<0.05) in multivariate regressions. Conclusion Patients who need treatment the most are at risk for dropouts and weight regain, emphasizing the need for interventions to reduce dropout and support inpatients after discharge. Furthermore, this study is the first to report that pre-treatment leptin and adiponectin levels predict post-treatment BMI SDS regain.